Prolyl-4-hydroxylase Α subunit 2 (P4HA2) expression is a predictor of poor outcome in breast ductal carcinoma in situ (DCIS) - Toss, Michael S. (Br J Cancer, 2018)
BACKGROUND: Extracellular matrix (ECM) plays a crucial role in tumour behaviour. Prolyl-4-hydroxlase-A2 (P4HA2) is a key enzyme in ECM remodelling. This study aims to evaluate the prognostic significance of P4HA2 in breast ductal carcinoma in situ (DCIS). METHODS: P4HA2 expression was assessed immunohistochemically in malignant cells and surrounding stroma of a large DCIS cohort comprising 481 pure DCIS and 196 mixed DCIS and invasive carcinomas. Outcome analysis was evaluated using local recurrence free interval (LRFI). RESULTS: High P4HA2 expression was detected in malignant cells of half of pure DCIS whereas its expression in stroma was seen in 25% of cases. Higher P4HA2 expression was observed in mixed DCIS cases compared to pure DCIS both in tumour cells and in stroma. High P4HA2 was associated with features of high risk DCIS including younger age, higher grade, comedo necrosis, triple negative and HER2-positive phenotypes. Interaction between P4HA2 and radiotherapy was also observed regarding the outcome. High P4HA2 expression was an independent prognostic factor in predicting shorter LRFI. CONCLUSION: P4HA2 plays a role in DCIS progression and can potentially be used to predict DCIS outcome. Incorporation of P4HA2 with other clinicopathological parameters could refine DCIS risk stratification that can potentially guide management decisions.